Evaluation of the cleaning efficacy of a normal toothbrush and a manual U shaped toothbrush in children aged 8–10 years: A randomized crossover trial - Shital Kiran Davangere Padmanabh; Vishakha Bhausaheb Gangurde (SRM Journal of Research in Dental Sciences)
Background: Plaque removal rates are influenced by toothbrush design as well as brushing methods. Aim: The study aimed to determine the efficacy of a manual U-shaped toothbrush when compared to a regular toothbrush in removing dental plaque from teeth in children aged 8–10 years. Materials and Methods: Our research included 40, 8–10-year-old children. Stage I included days 0–7, while Stage II covered days 8–15. A disclosing agent was used to identify and score the dental plaque. During Stage I of the study, Group I was given a regular toothbrush, and Group II was given a U-shaped toothbrush. During Stage II of the study, the cross-over of interventions was carried out. Loe-Silness gingival index and Turesky modification of the Quigley-Hein index were measured on the 8th and 16th day. Unpaired t-test/independent samples t-test were performed for comparison between the groups. Results: The intergroup evaluation of plaque scores on various surfaces between the two groups revealed statistically significant differences (P = 0.05) between the mean plaque scores at stage I on the labial surface (P = 0.001) and the lingual surface (P = 0.002) between the two groups. Comparing gingival health scores of various surfaces between the two groups, mesial, labial, distal, and lingual surfaces revealed statistically significant differences (P = 0.05) at stage II and lingual surfaces at stage I and stage II, respectively. Conclusion: The experimental U-shape toothbrush significantly reduced the extent of plaque on the lingual surfaces and improved the gingival index scores, which helped improve gingival health and oral hygiene.